Milk fatty acid profile of Indian dairy cows reared under organic and conventional feeding management - MAITY, S B; KUSHWAHA, B P; SINGH, SULTAN; KUMAR, ANIL; NAG, S K; DAS, S K; RAI, A K; DIXIT, A K (The Indian Journal of Animal Sciences, 2021)
In this study, milk fat content and milk fatty acid profile of 3 Indian dairy cattle breeds, viz. Sahiwal, Tharparkar and Gir was studied under organic and conventional feeding system. Milk fat content differed significantly among the breeds and varied from 3.74 to 4.57% across the breeds, however the feeding system did not influence the milk fat contents. Fatty acids contents were similar among breeds and feeding systems, however, the unsaturated fatty acids were comparatively higher in organic feeding system.